Diagnostic accuracy of intraoperative brainstem auditory evoked potential for predicting hearing loss after vestibular schwannoma surgery - Gu, Feng; Yang, Xingyu; Wang, Zilan; Tan, Xin; Xue, Tao; Chen, Zhouqing; Wang, Zhong; Chen, Gang (Frontiers in Neurology, 2022)
Objective We did a meta-analysis to study the diagnostic value of intraoperative brainstem auditory evoked potentials (BAEP) in predicting postoperative hearing loss. Methods Researches on MEDLINE, EMBASE database and Cochrane Library were searched and selected up to 20 Jan 2022 and data was extracted following a standard procedure. A diagnostic accuracy test meta-analysis using a mixed-effect binary regression model was performed. Results A total of 693 patients from 15 studies were extracted. The change of intraoperative BAEP showed a high estimate of sensitivity (0.95) with a low specificity (0.37). The area under the curve was 0.83. Diagnostic accuracy of the loss of potentials showed high estimates of sensitivity (0.82) and specificity (0.79). The area under the curve was 0.88. No factor was found responsible for the heterogeneity of the result according to the meta-regression and subgroup analysis (All P-value >0.05). Conclusions Our results show the loss of BAEP showed a meaningful value in predicting hearing loss after vestibular schwannoma surgery. Meanwhile the change of the potentials should be attached importance for its high sensitivity in the hearing preservation surgery.